Roadmap to Sustainable Textiles and Clothing Eco-friendly Raw Materials, Technologies, and Processing Methods - Muthu, Subramanian Senthilkannan (Textile Science and Clothing Technology, 2014)
This book covers the elements involved in achieving sustainability in the textiles and clothing sector. The chapters covered in different volumes of this series title aim to cover all the distinctive areas earmarked for achieving sustainable development in the textile and clothing industry. This first volume is dedicated to the initial phases of life cycle, i.e. raw materials and manufacturing phases of textile products. This book aims to cover the sustainable raw materials, technologies and processing methods to achieve sustainable textile products. There are plenty of raw materials available today to cater the needs of sustainable textiles and apparels including organic materials, recycled and biodegradable raw materials for textile applications. Similarly, many innovative methods to process textile materials to achieve sustainability in the supply chain along with various processing technologies to manufacture textile products sustainably. This first volume covers the titles of these areas in a comprehensive way.